The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3892/etm.2021.9966
|View full text |Cite
|
Sign up to set email alerts
|

Teratogenic effect of isotretinoin in both fertile females and males (Review)

Abstract: Isotretinoin is an oral derivate of vitamin A that has been used since 1982 for the treatment of multiple dermatologic conditions such as severe acne, rosacea, scarring alopecia, ichthyosis or non-melanoma skin cancer prophylaxis. The recommended dose is 0.5-1 mg/kg/day for a period of 4-6 months in sebaceous gland pathologies. There are many adverse effects caused by isotretinoin but by far the most important is the teratogenicity induced by this drug which is estimated to have a 20-35% risk to infants that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 52 publications
0
26
0
Order By: Relevance
“…The drastic change in erythropoiesis in bone marrow induced by ISO treatment would affect fluctuations of %PCE or % MNPCE per non-micronucleated erythrocytes in the MN test. It is known that the ISO achieves remarkable pharmacological efficacy in the treatment of severe acne, by influencing the basic cellular processes such as division, growth, survival, differentiation, and apoptosis (Tsukada et al, 2000;Rigopoulos et al, 2010;Miura, 2011;Nelson et al, 2011;Layton, 2014;Melnik, 2017;Draghici et al, 2021). Finally, it is worth mentioning that ISO and its analog structures tretinoin, and 4-oxo-isotretinoin are the major systemic metabolites identified in systemic circulation following oral administration of ISO (Colburn et al, 1983), and its plasma concentration is about 4-fold higher than that of the parent drug after multiple dosing (Sadeghzadeh-Bazargan et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The drastic change in erythropoiesis in bone marrow induced by ISO treatment would affect fluctuations of %PCE or % MNPCE per non-micronucleated erythrocytes in the MN test. It is known that the ISO achieves remarkable pharmacological efficacy in the treatment of severe acne, by influencing the basic cellular processes such as division, growth, survival, differentiation, and apoptosis (Tsukada et al, 2000;Rigopoulos et al, 2010;Miura, 2011;Nelson et al, 2011;Layton, 2014;Melnik, 2017;Draghici et al, 2021). Finally, it is worth mentioning that ISO and its analog structures tretinoin, and 4-oxo-isotretinoin are the major systemic metabolites identified in systemic circulation following oral administration of ISO (Colburn et al, 1983), and its plasma concentration is about 4-fold higher than that of the parent drug after multiple dosing (Sadeghzadeh-Bazargan et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The exact mechanism of the therapeutic action of ISO remains unknown. However, several studies have shown that this drug induces apoptosis in sebaceous gland cells (Melnik, 2017;Reigada et al, 2017;Draghici et al, 2021). The use of retinoids in cancer therapy is restricted because of their severe cytotoxic reactions, particularly if administered systemically in aqueous solutions (Diniz et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retinoids are structurally and functionally related to vitamin A [ 14 ] with proven functions in the skin based on the modulation of epidermal maturation, as well as keratinocyte differentiation, apoptosis, immune function and carcinogenesis [ 15 , 16 ]. Moreover, isotretinoin was found to induce apoptosis and cell cycle arrest in human sebocytes [ 17 ]. As a result, retinoids decrease thickening and scaling of the skin, decrease erythema [ 14 , 18 ] and facilitate wound healing [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…This points to the influence of this drug on hormonal changes in females. Evidence shows that isotretinoin, due to its derivation from vitamin A, is highly teratogenic and is therefore strictly contraindicated in women of reproductive age unless effective contraception is taken, often in the form of oral contraceptive pills [ 24 , 25 ]. A study done by Peck et al reported that in patients treated with isotretinoin, no changes in hormone levels were seen, suggesting a different cause for menstruation irregularities [ 26 ].…”
Section: Discussionmentioning
confidence: 99%